2006
DOI: 10.1152/jn.00105.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Preventing Sustained Activation of Cortex During Subcortical High-Frequency Stimulation

Abstract: . Kiss. Cellular mechanisms preventing sustained activation of cortex during subcortical high-frequency stimulation. J Neurophysiol 96: 613-621, 2006. First published March 22, 2006 doi:10.1152/jn.00105.2006. Axonal excitation has been proposed as a key mechanism in therapeutic brain stimulation. In this study we examined how high-frequency stimulation (HFS) of subcortical white matter tracts projecting to motor cortex affects downstream postsynaptic responses in cortical neurons. Whole cell recordings were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 47 publications
12
60
0
Order By: Relevance
“…Interestingly, the phase-locked excitatory responses to stimulation that we observed with delays Ͻ2 ms and with relatively low jitter, which could be attributable to antidromic activation, also showed an inability to entrain one to one with high-frequency stimulation. This finding is consistent with a study in brain slices showing that high-frequency stimulation of the motor thalamus could only entrain antidromic activity within corticothalamic axons at firing rates Ͻ50 Hz (Iremonger et al 2006). Similar findings have been reported for other axonal pathways (Jensen and Durand 2009;Rosenbaum et al 2014;Zheng et al 2011) although some fiber tracts, particularly heavily myelinated tracts, can follow high-frequency stimulation pulse trains (Chomiak and Hu 2007).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, the phase-locked excitatory responses to stimulation that we observed with delays Ͻ2 ms and with relatively low jitter, which could be attributable to antidromic activation, also showed an inability to entrain one to one with high-frequency stimulation. This finding is consistent with a study in brain slices showing that high-frequency stimulation of the motor thalamus could only entrain antidromic activity within corticothalamic axons at firing rates Ͻ50 Hz (Iremonger et al 2006). Similar findings have been reported for other axonal pathways (Jensen and Durand 2009;Rosenbaum et al 2014;Zheng et al 2011) although some fiber tracts, particularly heavily myelinated tracts, can follow high-frequency stimulation pulse trains (Chomiak and Hu 2007).…”
Section: Discussionsupporting
confidence: 90%
“…In theory, in the case of M1 activity during VPLo DBS, sustained excitation could also be limited by increased inhibition via disynaptic activation of inhibitory interneurons, which may sustain higher firing frequencies (Martina and Jonas 1997) and are less susceptible to conduction failure compared with glutamatergic neurons (Meeks and Mennerick 2004). However, as Iremonger et al (2006) noted, cortical neurons are still unable to follow the high-frequency pattern of stimulation even in the presence of GABA blockade. In addition, at high frequencies of stimulation, synaptic transmission is likely to undergo at least partial vesicle depletion (Anderson et al 2006), which was suggested to shape the cortical response to high-frequency thalamic stimulation in slices using a voltage-sensitive dye (Urbano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, there is some evidence for a sparse but direct cortical innervation of the pallidum (Naito and Kita 1994;Smith and Wichmann 2014). The low fidelity of driving observed here (spikes elicited by ϳ6% of shocks) is consistent with a previous study of antidromic activation of cortical neurons during high-frequency stimulation (Iremonger et al 2006). The paucity of stimulation driven high-frequency resonance in our recordings, combined with pronounced and persistent therapeutic effects of GPi-DBS, is inconsistent with the idea that antidromic-driven resonance in cortex is a primary therapeutic mechanism of action for GPi-DBS.…”
Section: Discussionsupporting
confidence: 80%